VETERINARY BIOSECURITY IN LIVESTOCK FARMS - Klichov Odil Ilkhomovich (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract. In this article, the rules of biosecurity in livestock farms, sanitary control of animals in farms, control of water and air pollution, ensuring the quality and safety of food raw materials and food production equipment, as a result of the activities of animal product processing enterprises information about the generated biological waste is given.